Modelling the interaction between railway wheel and rail - Dailydka, Stasys; Lingaitis, Leonas P.; Myamlin, Sergey; Prichodko, Vladimir (Transport, 2008)
The article presents a mathematical model for assessing the real operating conditions of railway rolling stock, taking into account the situations when the wheel loses contact with rail. The obtained amplitudinal fluctuation characteristics depend on the set roughness function and the running speed of the wheel. When calculating dynamic processes, the contact between wheel and rail should be considered unstable. With the increase of speed, the impact of this instability increases. First published online: 27 Oct 2010